OVERVIEW OF RECYCLING RUBBER TIRE AS AGGREGATES IN CONCRETE: AN APPROACH FOR SOLID WASTE MANAGEMENT - Al Adwan, Jamal; Alzubi, Yazan (Journal of Engineering & Technological Advances, 2022)
The difficulties related to non-biodegradable waste management raise the danger of environmental and health issues since millions of worn rubber tires are discarded yearly. Over the past several years, the building industry has been compelled to use this material combined with cement-based products due to the material’s accessibility and vast manufacturing volume. Due to its promising properties, including enhanced ductility, damping ratio, and vibration resistance, recycling used tire rubber as a partial replacement of natural stones in concrete is a topic of intense research. Conversely, the rubber aggregator reduces the mechanical characteristics and workability of the resulting concrete mixtures. This study reviews the feasibility of using shredded rubber tire waste as a partial replacement for traditional aggregates in concrete. The properties of the rubberized concrete are discussed with respect to various ratios of rubber tire waste and traditional aggregates. The results of previous studies showed that using rubber tire waste as an aggregate in concrete significantly reduces the mechanical properties of the concrete, including its compressive strength, tensile strength, and flexural strength. On the other hand, using rubber tire waste as an aggregate reduces the weight of the concrete, which may have potential benefits for structural design. Overall, the study suggests that recycling rubber tire waste as an aggregate in concrete is a viable approach for solid waste management and can also provide environmental and economic benefits.